Peran Partisipasi Orang Tua dalam Meningkatkan Motivasi Belajar Mata Pelajaran Akidah Ahlak Menggunakan Metode Imtaq - Ayatullah Ayatullah (AS-SABIQUN, 2022)
Participation is about taking part in an activity or participation or participation. Participation is the mental and emotional involvement of a person in a group situation that encourages them to contribute to the achievement of the goals of the group and take responsibility for the group. Huneryear and Hecman also stated that participation is the mental and emotional involvement of individuals in group situations that encourage them to contribute to group goals and share their shared responsibilities. Motivation is a change in energy in a person (personal) which is characterized by the emergence of feelings and reactions to achieve goals. Motivation is a force that drives individual activities to carry out an activity to achieve goals.